Graph-Based Methods for Clustering Topics of Interest in Twitter - Hromic, Hugo; Prangnawarat, Narumol; Hulpuş, Ioana; Karnstedt, Marcel; Hayes, Conor (Engineering the Web in the Big Data Era, 2015)
Online Social Media provides real-time information about events and news in the physical world. A challenging problem is then to identify in a timely manner the few relevant bits of information in these massive and fast-paced streams. Most of the current topic clustering and event detection methods focus on user generated content, hence they are sensible to language, writing style and are usually expensive to compute. Instead, our approach focuses on mining the structure of the graph generated by the interactions between users. Our hypothesis is that bursts in user interest for particular topics and events are reflected by corresponding changes in the structure of the discussion dynamics. We show that our method is capable of effectively identifying event topics in Twitter ground truth data, while offering better overall performance than a purely content-based method based on LDA topic models.